Ethics violations discourse of the Constitutional Court in Indonesian online media - Sulhan, Muhamad (Jurnal Studi Komunikasi, 2025)
This article analysed the discourse construction of online media following the Constitutional Court (MK) of the Republic of Indonesia's decision No.90/PUU-XXI/2023 in November 2023. Online media have addressed the controversy surrounding the ethical violations resulting from the MK's decision in various ways. Utilising the perspective of Critical Political Economy (CPE) on media institutions, this research assumes there is a diversity of content in online media when reporting on the ethical violations of the Chief Justice of the Constitutional Court. The research method employed is Corpus-Assisted Discourse Study (CADS) to analyse the frequency and discourse of news coverage from four online news portals (Tempo.co; Detik.com; Okezone.com; and Kompas.com) from November 1 to December 31, 2023. The findings indicate fluctuations in the frequency of word occurrences and dynamics of discourse in the news content that differ among the four online portals, which are related to the pragmatic interests of the media owners. The diversity in frequency and discourse regarding the ethical violation issues places the four studied media outlets within three corridors of tension in news orientation (normative-descriptive, moderate, and critical-radical).